An investigation into methods to develop indicators to measure injury related impairment. Issue 4 (9th August 2010) - Gulliver, Pauline; Cryer, Colin; Davie, Gabrielle; Langley, John
Abstract : Objective: To investigate whether valid indicators of injury-related impairment could be developed based on data from a New Zealand national no-fault accident insurance scheme. Design: The feasibility of (1) developing impairment related indicators using insurance data directly, and (2) deriving diagnosis specific probability of impairment measures based on hospital discharge data were investigated. Setting: The source data were lump sum payment data for permanent impairment arising from an injury event between 1 April 2002 and 31 October 2006, and hospital discharge data for injury events between 1 April 2002 and 31 December 2005. Main outcome measure: A threat of impairment measure was developed that was based on a list of International Classification of Diseases codes (version 10) which, if assessed would attract a lump sum payment for permanent impairment, and would almost always be expected to be admitted to hospital. Results: A group of approximately 80 diagnoses satisfying the above criteria were identified. The trend in age standardised injury rates for the threat of impairment indicator is consistent with the trend for the New Zealand threat to life indicator. Conclusions: This work has provided a method for the development of hospital discharge-based serious threat of impairment injury indicators. This is an important first step in developing a comprehensive package of (threat of) disability indicators.